Analysis and Flood Mapping of Pekalen Watershed of Probolinggo Regency Using HEC-RAS Application - Rossi Isnaina Annisa Hadi; Vita Ayu Kusuma Dewi (G-Tech: Jurnal Teknologi Terapan, 2025)
Flooding is one of the natural disasters that needs attention, especially in the Pekalen watershed, Probolinggo Regency. The purpose of this research is to analyze the design flood discharge and mapping of the area potentially affected by inundation. The research stages began with arithmetic area average rainfall analysis, log pearson type III design rainfall analysis, chi squared and smirnov-kolmogorov distribution fit test, mononobe rainfall intensity, HSS Nakayasu design flood discharge analysis, and flood mapping with HEC-RAS 2D flood modeling. The design flood discharge of Pekalen watershed at 10-year return period is 421.4 m³/s, 25-year return period is 455.12 m³/s, and 50-year return period is 479 m³/s. The areas potentially affected by inundation at 25 years return periods are Sukomulyo, Sukokerto, Pajarakankulon, Kradenan, Tanjung, Karangbong, Temenggungan, Karanggeger, Ketompen, Petemon, Selogudigwetan, Selogudigkulon, Puspan, Braniwetan, Branilor, Sumbersecang, Satreyan, Maronkidul, Gerongan, Brabe, Condong, Racek, Pesawaran, Ranugedang, Jangkang, Segaran, Ranuagung, Tiris, Andungsari, Andungbiru, and Sumberaren.